The urgency of Arctic change - Overland, James; Dunlea, Edward; Box, Jason E.; Corell, Robert; Forsius, Martin; Kattsov, Vladimir; Olsen, Morten Skovgård; Pawlak, Janet; Reiersen, Lars-Otto; Wang, Muyin (Polar Science, 2022)
This article provides a synthesis of the latest observational trends and projections for the future of the Arctic. First, the Arctic is already changing rapidly as a result of climate change. Contemporary warm Arctic temperatures and large sea ice deficits (75% volume loss) demonstrate climate states outside of previous experience. Modeled changes of the Arctic cryosphere demonstrate that even limiting global temperature increases to near 2 °C will leave the Arctic a much different environment by mid-century with less snow and sea ice, melted permafrost, altered ecosystems, and a projected annual mean Arctic temperature increase of +4 °C. Second, even under ambitious emission reduction scenarios, high-latitude land ice melt, including Greenland, are foreseen to continue due to internal lags, leading to accelerating global sea level rise throughout the century. Third, future Arctic changes may in turn impact lower latitudes through tundra greenhouse gas release and shifts in ocean and atmospheric circulation. Arctic-specific radiative and heat storage feedbacks may become an obstacle to achieving a stabilized global climate. In light of these trends, the precautionary principle calls for early adaptation and mitigation actions.